DISTORTIONS IN IKU-BASED PERFORMANCE MEASUREMENT SYSTEMS: AN EMPIRICAL STUDY ON KPP PRATAMA - Lis Mintarti; Siti Mujanah; Abdul Halik (Journal of Industrial Engineering & Management Research, 2026)
This study aims to evaluate the effectiveness of a performance measurement system based on Key Performance Indicators (KPIs) in representing organizational performance in the Primary KPP for the 2023–2025 period. In contrast to previous research that focused on aggregate achievements, this study focused on the analysis of indicator design, weighting systems, and potential distortions in performance measurement. The research uses a quantitative approach with a descriptive-evaluative method and utilizes secondary data in the form of performance indicator achievements. The analysis includes descriptive analysis, trends, and gaps between indicators. The results showed that despite the high aggregate achievement, there was a significant imbalance between the indicators that indicated distortion. This study concludes that the effectiveness of the measurement system is not only determined by the achievements, but also by the quality of the indicator design, weighting, and balance between performance components.